PENGARUH TINGKAT KEMATANGAN DAN KONSENTRASI CaCl2 TERHADAP KARAKTERISTIK FISIKOKIMIA DAN TINGKAT KESUKAAN FRENCH FRIES PISANG GOROHO (Musa acuminate L.) - Magdalena Utusan; Ir. Teltje Koapaha, MP.; Ir. Maya M. Ludong, MSi (COCOS, 2017)
AbstractThe research was aimed to determining the right level of maturity goroho bananaand concentration of CaCl2 on processing banana goroho french fries based onphysicochemical characteristics (texture, moisture content, the ash content, fat rate) andconsumer acceptance of goroho banana french fries product. This study used a factorialrandomized design with 2 factors, i.e : factor A were level of maturity goroho bananawith 3 level (80,90, and 100 days) and factor B were concentration of CaCl2 with 3 level(1%, 1.5%, and 2%). The parameters analysed were texture, moisture content, the ashcontent, fat rate and consumer acceptance including flavor, colour, smell and texture.The result of this research indicate that french fries with treatment of level 80 daysmaturity goroho banana and concentration CaCl2 1% (A1B1) had good consumeracceptance with physicochemical characteristic (texture 54.33 mm/g/second, moisturecontent 13.52%, the ash content 32.89% and fat rate 1.10%).Keyword : French fries, Goroho Banana, CaCl2